Growth response of cabbage (Brassica oleracea) to TiO2 nanoparticles exposure in Inceptisol of north-western mid-hills of Himachal Pradesh - BRAR, PERMINDER SINGH; BHARDWAJ, GITIKA; KAUSHAL, RAJESH; BHARDWAJ, RAMESH KUMAR; SINGH, UPENDER; SHARMA, UDAY (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted during 2020–21 and 2021–22 at Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh for assessing the effects of TiO2 (Titanium dioxide) nanoparticles on cabbage (Brassica oleracea L. var. capitata) growth, yield and economics under Agro-Climatic Zone- II of Himachal Pradesh. A field experiment was laid out in a randomized block dsesign (RBD) with three replications having 13 treatments , comprised of seed and foliar application of TiO2 nanoparticles (size